Open Dialogue: An Applied Laingian Practice (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
The ideas of Open Dialogue share a particular affinity with the work of R.D. Laing. Since Laing did not propose a therapeutic way of working with families with a psychotic or schizophrenic member, Open Dialogue may be as close as we get to an Applied Laingian approach.
Keywords: Open Dialogue; R.D. Laing; approach; psychotherapy; schizophrenia; intensive